Food insecurity is associated with morbidity and patterns of healthcare utilization among HIV-infected individuals in a resource-poor setting - Weiser, Sheri D.; Tsai, Alexander C.; Gupta, Reshma; Frongillo, Edward A.; Kawuma, Annet; Senkungu, Jude; Hunta, Peter W.; Emenyonue, Nneka I.; Mattson, Jennifer E.; Martin, Jeffrey N.; Bangsberg, David R. (AIDS (London, England), 2012)
We undertook a longitudinal study in rural Uganda to understand the association of food insecurity with morbidity and patterns of healthcare utilization among HIV-infected individuals enrolled in an antiretroviral therapy program. Longitudinal cohort study. Participants were enrolled from the Uganda AIDS Rural Treatment Outcomes cohort, and underwent quarterly structured interviews and blood draws. The primary predictor was food insecurity measured by the validated Household Food Insecurity Access Scale. Primary outcomes included health-related quality of life measured by the validated Medical Outcomes Study-HIV Physical Health Summary (PHS), incident self-reported opportunistic infections, number of hospitalizations, and missed clinic visits. To estimate model parameters, we used the method of generalized estimating equations, adjusting for sociodemographic and clinical variables. Explanatory variables were lagged by 3 months to strengthen causal interpretations.
Keywords: AIDS; Food insecurity; Healthcare utilization; HIV; Morbidity; Uganda